Wojownicy polscy w pierwszej wyprawie krzyżowej. Rozważania na podstawie powieści Krzyżowcy Zofii Kossak - Iwan Rajczew (Postscriptum Polonistyczne)
The article is devoted to the novel Crusaders (1935) by the Polish novelist Zofia Kossak (1889–1968). It discusses the author’s hypothesis about the Polish participation in the First Crusade (1096–1099). The article focuses on the possible interpretation of the novel in the spirit of the philosophy of Polish Messianism. The accession to the Crusade forces by the Silesian warriors can be considered as an act of redemption for the sins of the whole Polish nation as well as a pilgrimage to Poland being regarded as visiting the Promised Land. The psychological aspects of the first (according to the novel) participation of Polish armed forces in an international military expedition are also considered in terms of tribal solidarity, consolidating the role of Christianity and pagan traditions that had a significant impact on Poles at the end of the eleventh century.